Meningkatkan Kemampuan Berpikir Kritis Peserta Didik Pak dan BP Dengan Model PBL Pada Kelas VII SMP Budi Dharma Banda Aceh - Mentauli Simbolon; Mawarni Gea; Agustinus Mulyono (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This research is motivated by the lack of critical thinking skills of students during learning activities. This research was conducted using the Problem Based Learning model. The aim of this study is to improve the critical thinking skills of students with the Problem Based Learning model. The research method used is Classroom Action Research, the research process was conducted in two cycles. The subjects of the study were students of class X TAV SMK St. Louis Surabaya, with a total of 17 students. Data collection techniques in this study use observation and documentation. Data analysis techniques use comparative descriptive techniques by comparing data in cycle I and cycle II data. In conclusion, the application of the Problem Based Learning (PBL) Learning Model in the learning process has been proven to improve students' critical thinking competencies and learning achievements. Based on the results of observations in learning activities in cycle 1 and cycle 2, students' critical thinking skills have increased in number of students who have reached the category developing as expected and highly developed as many as 3 people where in cycle 1 there were 14 people and in cycle 2 became 17 people. The results of the formative test conducted also showed an increase in the average class score of 16.47 where in the formative test in cycle 1 the average class score was 63.53 and in cycle 2 the average class score became 80.